A bamboo-derived cellulose “high-speed rail” scaffold with gradient topology and temporal immunomodulation for tendon–bone interface regeneration - Yixuan Huang; Chen Chen; Hai Lan; Yichao Liu; Likun Liu; Heng Zhu; Lei Wang; Chenjian Peng; Hao Shu; Jiazhi Yang; Xin Liu; Luning Sun (Carbohydrate Polymers, 2026)

A Lorentzian decomposition and incremental learning framework for laser-induced breakdown spectroscopy of steels - Panyang Dai; Peichao Zheng; Jingjun Lin; Jinmei Wang; Guanghui Chen; Luning Li (Analytica Chimica Acta, 2026)

The importance of pro-environmental behavior in advancing sustainable tourism - Tiling Chen; Chao Ye; Lingjie Tang; H. Elhosiny Ali; Luning Lin; Youyou Zhu; Sana Togroi (Journal of Outdoor Recreation and Tourism, 2026)

A cellulosic waste-upcycled 1T/2H-MoS2/biochar heterostructure for efficient cationic dye adsorption via a multi-anchor chemisorption mechanism - Yifan Lu; Min He; Mingna Ge; Luning Chen; Lin Han; Cong Tu; Bang Yuan; Jie Huang (Journal of Environmental Chemical Engineering, 2026)

Integrated multi-omics and physiological analyses reveal mechanism of enhanced gellan gum biosynthesis in an ARTP-induced Sphingomonas paucimobilis mutant - Ling Sun; Shiyi Chen; Yazhen Wang; Lei Sun; Zejian Wang; Yong Zhou; Ali Mohsin; Suyang Li; Luning Zhao; Afira Nayab; Wenjing Sun (Food Microbiology, 2026)

Dual role of C60 in modulating oxygen vacancy and carrier dynamic: a novel strategy to enhance photothermal catalytic CO2 hydrogenation - Wanqing Zhang; Yaqin Wang; Zufeng Qiu; Luning Chen; Zhaoxiong Xie; Qin Kuang (Chemical Engineering Journal, 2025)

Structure of family health and its association with obesity-related eating behavior and depressive symptoms: Insights from network analysis - Junxu Lin; Zijuan Ma; Haihui Chen; Haoxian Ye; Wei Wang; Weishi Lin; Luning Yin; Rui Zhang; Dongfang Wang; Yunge Fan; Fang Fan (Appetite, 2025)

A dual-mode underwater robot with non-contact adsorption ability: Design, mode switching and field applications - Yanhu Chen; Suohang Zhang; Luning Zhang; Runmao Wu; Siyue Liu (Ocean Engineering, 2025)

Multifunctional dynamic chitosan-guar gum nanocomposite hydrogels in infection and diabetic wound healing - Luning He; Shuyi Xing; Weikang Zhang; Ying Wang; Yian Li; Jinghao Chen; Jinghai Zhang; Siling Wang; Qinfu Zhao (Carbohydrate Polymers, 2025)

Designing energy-efficient buildings in urban centers through machine learning and enhanced clean water managements - Ximo Chen; Zhaojuan Zhang; Azher M. Abed; Luning Lin; Haqi Zhang; José Escorcia-Gutierrez; Ahmed Ali A. Shohan; Elimam Ali; Huiting Xu; Hamid Assilzadeh; Lei Zhen (Environmental Research, 2024)

Biofilm growth enhancement in microalgae biofilm reactors: Parameters, configurations, and modeling - Luning Chen; Christopher T. DeGroot; Amarjeet Bassi (Journal of Water Process Engineering, 2024)

Granular sludge characterization and microbial response in a hydroxyapatite (HAP)- anammox coupled process at different nitrogen loading rates - Luning Wei; Yisong Hu; Yuemei Xue; Wenrui Tian; Yi Xue; Rong Chen (Journal of Water Process Engineering, 2024)

Biofouling recognition and boundary tracking control for underwater cleaning robots - Hang Su; Siyue Liu; Luning Zhang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2024)

Review of underwater adsorptive-operating robots: Design and application - Canjun Yang; Siyue Liu; Hang Su; Luning Zhang; Qingchao Xia; Yanhu Chen (Ocean Engineering, 2024)

The association between long-term exposure to outdoor artificial light at night and poor sleep quality among Chinese veterans: A multi-city study - Xinyi Sun; Jiping Tan; Yan Chen; Yuewei Liu; Guang-Hui Dong; Bo-Yi Yang; Nan Li; Luning Wang; Shanshan Li; Gongbo Chen; Yuming Guo (International Journal of Hygiene and Environmental Health, 2023)

Origin of the southern Ryukyu Forearc Terrace: A seaward-protrusion of arc crust elevated by subducted asperities? - Luning Shang; Gang Hu; Yongtao Chen; Chuansheng Yang; Yong Zhang (Journal of Asian Earth Sciences, 2023)

Performance study of energy conversion system for ocean thermal profiler - Yanhu Chen; Bingzhe Chen; Meiling He; Luning Zhang; Qingchao Xia; Canjun Yang (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.

New approach for designing an underwater free-space optical communication system - Yanhu Chen; Luning Zhang; Yucheng Ling (Frontiers in Marine Science, 2022)
Ocean observation system that involves multiple underwater vehicles and seafloor nodes plays an important role in better learning the ocean, where underwater wireless communication is mandatory for massive data interaction. Optical communication that has wide bandwidth and comprehensive working distance is the preferred method compared to acoustic and other methods. However, the presence of directionality makes the optical method difficult to use especially when the transceiver is equipped on a motive vehicle. In this study, an underwater free-space optical communication method of transmitting information is proposed. Characteristics of underwater optical transmission, as well as the photoelectric signal processing and modulation and demodulation algorithms, are studied and modeled. New approach for realizing underwater free-space optical communication is proposed and simulated. A prototype including a free-space optical transmitter and a receiver is developed; tests in different scenarios were carried out, and the results were observed: (1) by using the minimum number of LEDs, the effect of uniform lighting in space is achieved, and the transmitter coverage reaches 160°. (2) When the power of the transmitter is 10 W and the communication rate is 1 Mbps, the maximum communication distance reaches 13 m.

Accurate Fish Detection under Marine Background Noise Based on the Retinex Enhancement Algorithm and CNN - Yanhu Chen; Yucheng Ling; Luning Zhang (Journal of Marine Science and Engineering, 2022)
Underwater detection equipment with fish detection technology has broad application prospects in marine fishery resources exploration and conservation. In this paper, we establish a multi-scale retinex enhancement algorithm and a multi-scale feature-based fish detection model to improve underwater detection accuracy and ensure real-time performance. During image preprocessing, the enhancement algorithm combines the bionic structure of the fish retina and classical retinex theory to filter out underwater environmental noise. The detection model focuses on improving the detection performance on small-size targets using a deep learning method based on a convolutional neural network. We compare our method to current mainstream detection models (Faster R-CNN, RetinaNet, YOLO, SSDetc.), and the proposed model achieves better performance, with a mean Average Precision (mAP) of 78.31% and a mean Miss Rate (mMR) of 54.11% in the open fish image data set. The test results for the data from the field experiment prove the feasibility and stability of our model.

Soil fungal taxonomic diversity along an elevation gradient on the semi-arid Xinglong Mountain, Northwest China - Salman Khan; Ning Chen; Cankun Zhang; Luning Wang; Chun Han; Kanglong Lu; Yage Li; Muhammad Rafiq; Awais Iqbal; Changming Zhao (Archives of Microbiology, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Microbial degradation of organophosphorus pesticides: novel degraders, kinetics, functional genes, and genotoxicity assessment - Bo Jiang; Nana Zhang; Yi Xing; Luning Lian; Yating Chen; Dayi Zhang; Guanghe Li; Guangdong Sun; Yizhi Song (Environmental Science and Pollution Research, 2019)

Increased drought and atmospheric CO2 positively impact intrinsic water use efficiency but do not promote tree growth in semi-arid areas of northwestern China - Kanglong Lu; Ning Chen; Xiaowei Zhang; Jingru Wang; Minghao Wang; Salman Khan; Chun Han; Cankun Zhang; Shuyuan Wang; Luning Wang; Wenting Gao; Yongjing Liu; et al. (Trees, 2019)

Advances of magnetic nanoparticles in environmental application: environmental remediation and (bio)sensors as case studies - Bo Jiang; Luning Lian; Yi Xing; Nana Zhang; Yating Chen; Pei Lu; Dayi Zhang (Environmental Science and Pollution Research, 2018)

Regulatory properties of malic enzyme in the oleaginous yeast, Yarrowia lipolytica, and its non-involvement in lipid accumulation - Huaiyuan Zhang; Luning Zhang; Haiqin Chen; Yong Q. Chen; Colin Ratledge; Yuanda Song; Wei Chen (Biotechnology Letters, 2013)

Analysis of recoverable waste heat of circulating cooling water in hot-stamping power system - Panpan Qin; Hui Chen; Lili Chen; Chong Wang; Xiaoxiao Liu; Xiaojie Hu; Luning Yu; Shikui Liu (Clean Technologies and Environmental Policy, 2013)